Faktor Penentu Aksesibilitas Pembiayaan Bank Wakaf Mikro pada Pelaku Usaha Mikro di Jawa Timur - Diniyah, Fellasufah; Widjaja, Muhammad Yusuf Aria; Syafira, Suci Reza (DPPM Universitas Pelita Bangsa, 2025)
This study aims to determine the factors that determine the accessibility of financing at Micro Waqf Banks. The method used is a quantitative method, using primary data distributed to micro-entrepreneurs around Islamic boarding schools where Micro Waqf Banks (BWM) are located in East Java. The sample in this study consisted of 100 respondents, namely 75 respondents received financing accessibility and 25 respondents did not receive financing accessibility. Data analysis used in this study was logistic regression using Stata 16. The results of this study indicate that factors that influence financing accessibility at BWM are influenced by the variables of age, education, and assets, while the variables of household size, income, length of business, network or recommendation, and business mentoring do not affect micro-entrepreneurs in financing accessibility at BWM. The limitations or implications of this study are limited to data obtained from two districts or cities in East Java. However, the novelty in this study lies in the accessibility of financing at Micro Waqf Banks, which are LKMS whose funding sources come from social funds, namely waqf.